Influence of Water Treatment Sludge on the Growth of Coleus amboinicus - Muhamad, Siti Hajar Anaziah; Noh, Narita; Mohamad Yusri, Mohamad Faris (Advanced and Sustainable Technologies (ASET), 2026)
The accumulation of water treatment sludge (WTS) poses a significant environmental challenge, as traditional disposal methods, such as landfilling, are increasingly constrained by high costs and land scarcity. The objective of this preliminary study was to assess the potential and feasibility of utilizing WTS for plant cultivation, specifically by examining the growth of Coleus amboinicus across varying WTS amendment concentrations. The experimental design used four treatments: a control group (100% soil) and three amended groups with low, medium, and high WTS content, respectively. Plants were grown in pots under natural conditions for 54 days. Growth performance was quantified through weekly measurements of plant height and leaf size development. The results demonstrated a trend of improved plant vitality with increasing WTS content. Notably, the treatment with the highest WTS content showed the greatest growth in both height and leaf dimensions compared to the control and lower-concentration amendments. These findings suggest that water treatment sludge is viable for soil enhancement, offering a dual solution for waste management and aligning with SDG 12 while supporting SDG 15 through agricultural productivity and sustainable ecosystem management.